Immune Thrombocytopenic Purpura With Unusual Presentations – Reports of Two Cases - Chowdhury, Tasmina; Momen, Abdul Basit Ibne; Barman, Hironmoy; Khan, Mohammad Tariqul Ahsan; Begum, Kohinoor; Islam, Quazi Tarikul (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Immune thrombocytopenic purpura (ITP) is an immune mediated bleeding disorder, usually has a relatively benign clinical course. Deep seated bleeding like intracranial haemorrhage or haemoperitonium or massive haemorrhage requiring transfusion or other intervention are rare in ITP, unless platelet count are extremely low or other complicating conditions coexist. Here are two case reports of ITP presenting in uncommon and devastating manners. The 1st one is of a 21- yearold married nulliparaous lady with ITP complicating her undiagnosed ovarian hyperstimulation syndrome leading to haemoperitonium (ruptured ovarian cyst), post operative alveolar haemorrhage resulting in ARDS and later on DVT of right leg on her 9th POD. She was managed by multi discipline team. A new consequence of her disease one after another was striking and made her management more challenging. Ultimately the lady recovered and was discharged with advice which was not less than a miracle. The 2nd case is of a 50- year- old elderly lady who had a hemorrhagic stroke as a presenting feature of ITP. Though ITP is not an uncommon disease but in these cases its presentation, consequences and severity was unusual and making its management very much challenging. J Bangladesh Coll Phys Surg 2020; 38(4): 218-222